Match-play activity profile in elite women's rugby union players - Suarez-Arrones, L.; Portillo, J.; Pareja-Blanco, F.; Saez de Villarreal, E.; Sánchez-Medina, L.; Munguia-Izquierdo, D. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to provide an objective description of the locomotive activities and exercise intensity undergone during the course of an international-level match of female rugby union. Eight players were analyzed using global positioning system tracking technology. The total distance covered by the players during the whole match was 5,820 ± 512 m. The backs covered significantly more distance than the forwards (6,356 ± 144 vs. 5,498 ± 412 m, respectively). Over this distance, 42.7% (2,487 ± 391 m) was spent standing or walking, 35% jogging (2,037 ± 315 m), 9.7% running at low intensity (566 ± 115 m), 9.5% at medium intensity (553 ± 190 m), 1.8% at high intensity (105 ± 74 m), and 1.2% sprinting (73 ± 107 m). There were significant differences in the distance covered by forwards and backs in certain speed zones. Analysis of the relative distance traveled over successive 10-minute period of match play revealed that the greatest distances were covered during the first (725 ± 53 m) and the last (702 ± 79 m) 10-minute period of the match. The average number of sprints, the average maximum distance of sprinting, the average minimum distance of sprinting, and the average sprint distance during the game were 4.7 ± 3.9 sprints, 20.6 ± 10.5 m, 5.8 ± 0.9 -m, and 12.0 ± 3.8 m, respectively. There were substantial differences between forwards and backs. Backs covered greater total distance, distance in certain speed zones, and sprinting performance. The players spent 46.9 ± 28.9% of match time between 91 and 100% of maximum heart rate and experienced a large number of impacts (accelerometer data and expressed as g forces) during the game. These findings offer important information to design better training strategies and physical fitness testing adapted to the specific demands of female rugby union.